2018
DOI: 10.1111/ggi.13463
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening and frailty in Mexican older adults

Abstract: Telomere length is inversely related to frailty in Mexican frail older adults, and tobacco consumption is the main environmental modifying factor. Geriatr Gerontol Int 2018; 18: 1286-1292.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
3
4
2
Order By: Relevance
“…A first analysis was conducted to determine our hypothesized distinct distributions between oxidative stress, lipid peroxidation, and telomere length according to frailty groups; however, we observed a significantly different distribution only for telomere length. Telomere length was found to be associated with pre-frail and frail categories, as previously reported 12 . This specific variable has become of importance for older adults since, despite the philosophical debate about the definition of frailty, it has shown to have a predictive Figure 2.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A first analysis was conducted to determine our hypothesized distinct distributions between oxidative stress, lipid peroxidation, and telomere length according to frailty groups; however, we observed a significantly different distribution only for telomere length. Telomere length was found to be associated with pre-frail and frail categories, as previously reported 12 . This specific variable has become of importance for older adults since, despite the philosophical debate about the definition of frailty, it has shown to have a predictive Figure 2.…”
Section: Discussionsupporting
confidence: 86%
“…On the matter, telomere length, which has been associated with lifespan 9 , has had a controversial role in frailty description. Although no correlation was found for Chinese 10 and German 11 populations, we recently observed shorter telomeres associated with frailty in a Mexican population 12 .…”
Section: Introductioncontrasting
confidence: 68%
“…Other markers such as telomere length which has been associated with lifespan (Boonekamp, Simons, Hemerik, & Verhulst, 2013), have had a controversial role on frailty description. Although no correlation was found for Chinese (Yu, Tang, Leung, & Woo, 2015) and German (Breitling et al, 2016) populations, we recently observed shorter telomeres associated with frailty in a Mexican population (Ortiz-Ramírez et al, 2018).…”
Section: Background and Objectivescontrasting
confidence: 56%
“…38 Tobacco consumption is the main environmental modifying factor and is associated with telomere length and frailty in older adults. 39 Obesity, smoking, and aging act in concert to accelerate telomere loss.…”
Section: Genetic Factorsmentioning
confidence: 99%